Metabolic Cost and Mechanical Efficiency of a Novel Handle-Based Device for Wheelchair Propulsion - Markus Puchinger; Nithin Kurup; Karin Gstaltner; Marcus G. Pandy; Margit Gföhler (Journal of Rehabilitation Medicine, 2022)
Objective: To investigate differences in metabolic cost and gross mechanical efficiency of a novel handlebased wheelchair propulsion device and to compare its performance with conventional push-rim propulsion. Design: Double-group comparative study between 2 different propulsion methods. Participants: Eight paraplegic individuals and 10 non-disabled persons. Methods: Participants performed the same exercise using a push-rim device and the novel handle-based device on a wheelchair- based test rig. The exercise consisted of a combined submaximal and maximal test. Power output, oxygen uptake, ventilation, respiratory exchange ratio and heart rate were recorded continuously during the tests. Analysis of variance was performed to determine the effects of group, mode and on power output. Results: Submaximal exercise resulted in a higher efficiency for the novel device and significant main effects of propulsion mode on all investigated parameters, except heart rate. On the respiratory exchange ratio, a significant interaction effect was found for both mode and group. The maximal exercise resulted in a higher peak power output and lower peak heart rate during propulsion using the handle-based device. A significant main effect on mode for mean peak power output, ventilation and heart rate was also observed. Conclusion: Wheelchair propulsion using the handle-based device resulted in lower physical responses and higher mechanical efficiency, suggesting that this novel design may be well suited for indoor use, thereby offering an attractive alternative to pushrim wheelchairs.